Evaluasi Usability Sistem Informasi Penelitian dan Pengabdian Masyarakat Menggunakan Heuristic Evaluation dan Human-Centered Design - Efilda; Tengku Khairil Ahsyar; Muhammad Lutfhi Hamzah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Education is an asset for successfully building human resources in competition in the digital age. The world of education must increase the effectiveness of building education in this country in accordance with increasingly sophisticated technological advances such as the Information System for Research and Community Service (SIP). SIP is used to assist organizations in reporting work processes as operational achievements of external organizations as well as enabling task completion. The main problem with the SIP website is that it has never been evaluated in terms of usability since the system was used. This study aims to evaluate the usability of SIP websites using Heuristic Evaluation and Human-Centered Design. Usability is a very important factor for website acceptance. The Heuristic Evaluation uses 3 evaluators to assess the SIP website and uses 10 Heuristic Evaluation principles. The Human Centered Design method is used as a tool for developing designs and interactive systems that focus on user needs. From the results of the initial Heuristic Evaluation carried out by 3 evaluators by producing 21 problems as a basis for improving solution designs using prototypes. Furthermore, the second heuristic evaluation resulted in a decrease in problems, namely 3 problems located in the Heuristic code H1 Visibility Of System Status. This problem is a new problem found by evaluator 1. After doing a comparison, it can be concluded that the evaluation of the solution design resulted in a reduction of 18 problems from the 21 problems found to 3 problem findings found in the solution design evaluation